A Discontinuous Galerkin Method for Ideal Two-Fluid Plasma Equations (Communications in Computational Physics, 2018)
A discontinuous Galerkin method for the ideal 5 moment two-fluid plasmasystem is presented. The method uses a second or third order discontinuous Galerkinspatial discretization and a third order TVD Runge-Kutta time stepping scheme. Themethod is benchmarked against an analytic solution of a dispersive electron acousticsquare pulse as well as the two-fluid electromagnetic shock [1] and existing numericalsolutions to the GEM challenge magnetic reconnection problem [2]. The algorithm canbe generalized to arbitrary geometries and three dimensions. An approach to maintainingsmall gauge errors based on error propagation is suggested.